Pengaruh Self-Efficacy, Career Development, Dan Lingkungan Kerja Terhadap Kinerja Pegawai Kantor Kecamatan Gumukmas - Nuraini, Salsa Chandra; S, Ira Puspitadewi; Murtaliningtyas, Wenny (Training & Research Institute - Jeramba Ilmu Sukses, 2025)
This study aims to analyze in depth the influence of self-efficacy, career development, and work environment on employee performance at the Gumukmas District Office, Jember. Self-efficacy, which refers to an individual's belief in their ability to achieve certain results, is believed to significantly impact employee motivation and productivity. Meanwhile, career development includes various efforts made by individuals and organizations to improve employee skills, knowledge, and career opportunities, which can contribute to improved performance. On the other hand, a conducive work environment, including organizational culture, facilities, and support from coworkers, also plays a vital role in creating a supportive atmosphere for employees to achieve their best performance. The method used in this study is quantitative, which provides a systematic and measurable approach to data collection. The data collection process was carried out through several techniques, including direct observation in the work environment, interviews with employees to obtain qualitative information, and the distribution of questionnaires specifically designed to measure the variables studied. In addition, documentation related to employee performance and career development programs at the District Office was also analyzed to provide a broader context. The research sample consisted of 43 respondents, including ASN (State Civil Apparatus) and Non-ASN employees at the Gumukmas District Office. This sample selection aims to ensure the data obtained is representative so that the results of the study can be interpreted more accurately. The collected data were then analyzed using multiple linear regression with the help of SPSS version 27 software, which allows researchers to evaluate the relationship between independent variables (self-efficacy, career development, and work environment) with the dependent variable (employee performance). The analysis results show that self-efficacy, career development, and work environment positively and significantly influence employee performance at the Gumukmas District Office, Jember. This finding indicates that improvements in these three variables can directly contribute to improving employee performance. Therefore, it is recommended for the management of the Gumukmas District Office to continue to encourage the development of programs that can improve employee self-efficacy, provide better career development opportunities, and create a more supportive work environment, so that operational effectiveness at the sub-district level can increase overall.